Implementasi Metode Role Play Sosiodrama dalam Meningkatkan Pemahaman Perilaku Terpuji Materi Pendidikan Agama Islam Siswa Kelas II SDN 001 Bontang Selatan - Ariansyah, Rifky Ardi; Aslam, Muhammas (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to determine how the implementation of the sociodrama role play method improves the understanding of commendable behavior in the subject of Islamic Religious Education (PAI) for class II students of SDN 001 Bontang Selatan in the 2024/2025 Academic Year. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were analyzed using the Miles and Huberman interactive analysis model technique which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that the sociodrama role play method was able to improve students' understanding of commendable behavioral values such as honesty, helping each other, and responsibility. Students who were actively involved in sociodrama activities showed a better understanding, and were able to associate moral values in everyday life. Teachers and principals also considered this method effective in building a pleasant learning atmosphere, increasing student participation, and strengthening character formation through contextual learning. The conclusion of this study is that the sociodrama role play method is an effective learning strategy in improving students' understanding of commendable behavior in elementary schools, especially if implemented with full support from teachers and the school environment. The uniqueness (novelty) of this study lies in the application of the sociodrama method in the context of Islamic Religious Education learning for elementary school students, which has not been the focus of much previous research. This method is proven to not only convey values theoretically, but also shape attitudes through direct experience.